Influencing factors for ethnic tolerance among multi-ethnic youths - Ahmad, A.R.; Rahman, A.A.A.; Awang, M.M.; Chew, F.P. (2017)
This study aims at investigating factors that are contributing to ethnic tolerance among multiethnic youths. Four factors identified in this study were socio-environment, socio-participation, knowledge and practices of patriotism. Ethnic tolerance in this study can be defined as ethnic relations and the unity among myriad ethnic groups who practice a variety of cultures, religions and lifestyles which are different from each other and they can live together without feeling prejudiced at each other. Ethnic tolerance is also referring to the concept of integration in the context of ethnic diversity in multi-ethnic society in Malaysia (Syamsul Amri, 2012). This survey involved 2600 multi-ethnic youth aged between 19 and 29 years in Malaysia which comprises of Peninsular area (n = 1600), Sabah and Sarawak (n = 1000). Peninsular Zone was divided into four zones namely north, south, east and west. A set of questionnaires was used for data collection. A pilot study was carried out prior to data collection and the Cronbach alpha results indicating that the items for all contructs are valid and able to be used (0.806 and 0.953). Results from this study revealed that all factors had a significant relationship towards racial tolerance. Detailed fmdings show that socio-participation is the largest contributor towards tolerance (34.4%), followed by knowledge, practices and socio-environment, Hence, all parties have to work together to organize activities which can enhance the friendship relations between different races. Integrity, moral, and empathy should be employed by every individual in learning and practicing tolerance. The importance of tolerance as a social value can not be understated in the life of harmonious society.